THE ROLE OF PUBLIC RELATIONS IN CRISIS COMMUNICATION: A THEORETICAL ANALYSIS OF CORPORATE REPUTATION MANAGEMENT - Ajijola, Bashiru Amoda; Shiyanbola, Mahmood Olawale (African Journal of Social and Behavioural Sciences, 2025)
This study conducts a conceptual analysis to examine the role of public relations (PR) in crisis communication and corporate reputation management. The approach involves a conceptual synthesis of key crisis communication theories with illustrative corporate cases to analyze effective response strategies. It explores prominent theoretical frameworks, specifically Situational Crisis Communication Theory (SCCT), Image Repair Theory, and Excellence Theory, to provide insights into how organizations can mitigate reputational damage. This paper’s original contribution lies in demonstrating how the integration of these theories offers a more robust explanatory model for reputation recovery, particularly in the context of modern, social-media driven crises. The analysis of well-known corporate responses illustrates best practices for managing crises and protecting organizational value. This study concludes with theoretical and practical implications for PR practitioners seeking to enhance organizational resilience.